Composite current collector and preparation method and application thereof

By using composite fluid collection in the battery, combining the swelling polymer layer, polymer layer and metal layer, the problems of low energy density and low roller safety test pass rate are solved, and higher safety performance and pass rate are achieved.

CN119812350APending Publication Date: 2025-04-11DONGGUAN LIWINON ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411990576.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries are difficult to meet the demand for high energy density due to the low capacity of positive electrode materials and graphite negative electrodes. At the same time, the space gap inside the steel shell battery is too large, which affects the battery's drum safety test pass rate.

Method used

The composite fluid collector, including a swelling polymer layer, a polymer layer and a metal layer, is used to improve the contact effect between the electrode sheet and the electrode sheet and reduce the gap between the battery cell and the shell by the recombination of the polymer layer and the swelling polymer layer.

Benefits of technology

It effectively improves the battery's drum safety test pass rate, enhances the battery's safety performance, reduces the tensile stress between the poles, and reduces the loss of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812350A_ABST
    Figure CN119812350A_ABST
Patent Text Reader

Abstract

The invention discloses a composite current collector and a preparation method and application thereof, and belongs to the technical field of energy storage. The composite current collector provided by the invention comprises a swelling polymer layer, a polymer layer and a metal layer, the polymer layers are located on the surfaces of the two sides of the swelling polymer layer; the metal layers are located on the surfaces of the two sides of the polymer layer. According to the invention, the swelling polymer layer is arranged in the middle of the polymer layer, so that the swelling polymer layer replaces part of the polymer layer, and the swelling polymer layer expands after absorbing electrolyte based on the swelling characteristic of the swelling polymer, so that the contact effect between pole pieces can be improved, and the gap between the battery cell and the shell can be reduced; the problem of low qualified rate of the safety test of the battery roller is effectively solved. Through compounding of the polymer layer and the swelling polymer layer, the obtained composite current collector can effectively improve the safety performance of the battery, the safety test qualification rate of a battery roller is improved, and the composite current collector has a good application prospect in preparation of high-safety-performance positive pole pieces and batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage, and in particular relates to a composite current collector and a preparation method and application thereof. Background Art

[0002] As the demand for 3C consumer electronic products increases year by year, people have put forward higher requirements for the safety performance and energy density of lithium-ion batteries. In order to improve the safety performance of batteries while taking into account the cost, composite current collectors were proposed and have been successfully applied in battery products. However, limited by the low capacity of traditional positive electrode materials and graphite negative electrodes, traditional lithium-ion batteries are difficult to meet the current energy density requirements. Therefore, silicon-doped graphite negative electrodes have become a current research hotspot. Due to the large volume expansion of silicon during the cycle, in order to reserve space for the cycle expansion of silicon-doped batteries, when designing silicon-doped batteries, the battery cell size is smaller than that of traditional graphite negative electrode batteries. This situation is particularly evident in steel-shell batteries. This results in excessively large space gaps inside the steel-shell battery, which affects the battery's pass rate in the roller safety test. Summary of the invention

[0003] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a composite current collector, which can effectively solve the problem of low pass rate of drum test of batteries.

[0004] A second object of the present invention is to provide a method for preparing the above-mentioned composite current collector.

[0005] A third object of the present invention is to provide a positive electrode plate.

[0006] A fourth object of the present invention is to provide a battery.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a composite current collector, comprising a swollen polymer layer, a polymer layer and a metal layer; the polymer layer is located on both side surfaces of the swollen polymer layer; the metal layer is located on both side surfaces of the polymer layer.

[0009] Preferably, the swelling degree of the material of the swellable polymer layer is 50 to 200%, and more preferably 100 to 200%.

[0010] The degree of swelling refers to the ratio of the volume after swelling to the volume before swelling when the polymer molecules adsorb solvent molecules to reach swelling equilibrium.

[0011] Preferably, the material of the swelling polymer layer includes polystyrene; further preferably, the material of the swelling polymer layer is selected from polystyrene.

[0012] Polystyrene is a swelling polymer material with good swelling performance, which can absorb solvents and swell; its swelling degree is in the range of 100-200%. The present invention uses polystyrene as the material of the swelling polymer layer, which can not only absorb electrolyte expansion to improve the contact effect between the pole pieces and reduce the gap between the winding core and the shell, but also play an electrical insulation and supporting role. At the same time, after absorbing the electrolyte, it has a greater expansion and a more significant supporting role.

[0013] Preferably, the material of the polymer layer includes at least one of polyethylene terephthalate (PET), polypropylene (PP), polyethylene (PE), polyvinyl chloride (PVC) or polyimide (PI). In some embodiments of the present invention, the material of the polymer layer is selected from polyethylene terephthalate (PET).

[0014] Preferably, the material of the metal layer includes aluminum, copper or a combination thereof. In some embodiments of the present invention, the material of the metal layer is selected from aluminum (Al).

[0015] Preferably, the ratio of the thickness of the swollen polymer layer to the single layer thickness of the polymer layer is 1:(0.1-6); more preferably 1:(0.4-5); further preferably 1:(0.7-4); for example, it can be 1:0.8, 1:0.9, 1:1, 1:2, 1:3, 1:4.

[0016] Maintaining a certain thickness ratio between the swelling polymer layer and the polymer layer can achieve a better composite effect, promote a better swelling effect of the composite current collector, and a higher roller test pass rate; it can further reduce the cyclic lithium plating phenomenon of the battery during operation.

[0017] Preferably, the ratio of the thickness of the swollen polymer layer to the single layer thickness of the metal layer is 1:(0.1-3); more preferably 1:(0.2-2); further preferably 1:(0.3-1.5); for example, it can be 1:0.3, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5.

[0018] Preferably, the thickness of the swollen polymer layer is 0.5 to 5 μm; more preferably, it is 0.8 to 4 μm; and even more preferably, it is 1 to 3 μm.

[0019] Preferably, the single layer thickness of the polymer layer is 1 to 3 μm; more preferably, it is 1.2 to 2.75 μm; and even more preferably, it is 1.5 to 2.5 μm.

[0020] Preferably, the single layer thickness of the metal layer is 0.5 to 2 μm; more preferably, it is 0.7 to 1.5 μm; and even more preferably, it is 0.8 to 1.2 μm.

[0021] The second aspect of the present invention provides a method for preparing a composite current collector as described in the first aspect of the present invention, comprising the following steps: preparing a polymer layer; modifying the surface of one side of the polymer layer, preparing a swollen polymer layer on the surface of the modified polymer layer, and composite the swollen polymer layer with the surface of another modified polymer layer; modifying the surface of the other side of the polymer layer, preparing a metal layer on the surface of the modified polymer layer to obtain the composite current collector.

[0022] Preferably, the modification treatment comprises at least one of corona treatment, plasma treatment or chemical treatment. In some embodiments of the present invention, the modification treatment is selected from corona treatment; in some specific embodiments of the present invention, the corona treatment is performed until the corona value of the material surface is ≥50 dynes.

[0023] Modifying the surface of the polymer layer can help it to better combine with the swelling polymer layer and the metal layer.

[0024] A third aspect of the present invention provides a positive electrode plate, wherein raw materials for preparing the positive electrode plate include positive electrode slurry and the composite current collector described in the first aspect of the present invention.

[0025] The fourth aspect of the present invention provides a battery, comprising a positive electrode plate, an electrolyte and a negative electrode plate; the positive electrode plate is selected from the positive electrode plate described in the third aspect of the present invention.

[0026] The positive electrode sheet and the battery made by the composite current collector provided by the present invention both have good safety performance, and the battery has a high pass rate in the roller safety test.

[0027] The beneficial effects of the present invention are as follows: the present invention sets a swelling polymer layer in the middle of the polymer layer, so that the swelling polymer layer replaces part of the polymer layer. Based on the expansion characteristics of the swelling polymer, it expands after absorbing the electrolyte, which can improve the contact effect between the pole pieces and reduce the gap between the battery cell and the shell, effectively solving the problem of low pass rate of the battery roller safety test. The composite current collector obtained by compounding the polymer layer and the swelling polymer layer can effectively improve the safety performance of the battery and increase the pass rate of the battery roller safety test, and has good application prospects in the preparation of positive pole pieces and batteries with high safety performance.

[0028] Specifically, compared with the prior art, the present invention has the following advantages:

[0029] 1. Since the battery will expand in volume and squeeze the current collector in the later stage of the cycle, the swollen polymer layer has good tensile properties after absorbing liquid and swelling, which can play a buffering role, thereby reducing the tensile stress between the pole pieces. At the same time, after squeezing, the polymer layer can also partially release the absorbed electrolyte to reduce the loss of electrolyte.

[0030] 2. The polymer layer and the swollen polymer layer are both electrically insulating and play a supporting role. Among them, the polymer layer plays a supporting role in the composite current collector and has a low expansion effect. The introduction of the swollen polymer layer not only plays a supporting role, but also has a more significant supporting effect after absorbing the electrolyte due to its large expansion. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the structure of a composite aluminum foil in the prior art.

[0032] Figure 2 Schematic diagram of the structure of the composite current collector in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0033] The composite current collector used in the existing industry is a composite aluminum foil structure, which is a "sandwich" structure, with the inner layer being a polymer high molecular layer (such as PET, PP or PI, etc.) and the two sides being metal conductive layers (such as Al, etc.). At present, the industrialized composite aluminum foil uses 6μm PET (polyethylene terephthalate) as the substrate for the internal high molecular layer, and then evaporates 1μm aluminum metal layers on both sides of the substrate. Figure 1 It is a schematic diagram of the structure of a composite aluminum foil in the prior art, 1 is a PET base film layer, and 2 is an Al layer.

[0034] In the battery prepared by the composite aluminum foil in the above prior art, the space gap inside the steel shell battery is too large, which will greatly affect the battery's pass rate in the roller safety test. In order to solve the problem of low pass rate of steel shell battery roller safety test, the technical solution of the present invention is proposed.

[0035] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0036] Example 1

[0037] A composite current collector, consisting of a swelling polymer layer 3, two PET layers 1 and two Al layers 2; the PET layer 1 is located on both sides of the swelling polymer layer 3; the Al layer 2 is located on both sides of the PET layer 1. The schematic diagram of its structure is shown in FIG. Figure 1 As shown, 1 is a PET layer, 2 is an Al layer, and 3 is a swelling polymer layer. The swelling polymer layer is made of polystyrene.

[0038] The specific preparation steps of the above composite current collector are as follows:

[0039] (1) A PET polymer is prepared by esterification and polycondensation of phthalic acid and ethylene glycol. After drying and plasticization, a polymer high molecular PET substrate with a thickness of 2.75 μm is obtained.

[0040] (2) Take two PET substrates and perform corona treatment on one side of each substrate, with the corona value being ≥50 dynes.

[0041] (3) Melting the swollen polymer polystyrene particles, applying the polystyrene melt with a thickness of 0.5 μm on one side of the PET substrate after surface treatment through an extrusion device to obtain a swollen polymer polystyrene layer; and then compounding the other side of the swollen polymer polystyrene layer with one side of another PET substrate after surface treatment to obtain a composite polymer substrate.

[0042] (4) The untreated surfaces of the two PET layers in the composite polymer substrate are subjected to corona treatment, and then a metal aluminum layer with a thickness of 1 μm is vacuum evaporated on the treated surfaces to obtain a composite current collector.

[0043] Example 2

[0044] This example provides a composite current collector, which is different from Example 1 in that the thickness of the PET layer on one side of this example is 2.5 μm, the thickness of the swollen polymer layer is 1 μm, and the rest is the same as Example 1.

[0045] Example 3

[0046] This example provides a composite current collector, which is different from Example 1 in that the thickness of the PET layer on one side of this example is 2 μm, the thickness of the swollen polymer layer is 2 μm, and the rest is the same as Example 1.

[0047] Example 4

[0048] This example provides a composite current collector, which is different from Example 1 in that the thickness of the PET layer on one side of this example is 1.5 μm, the thickness of the swollen polymer layer is 3 μm, and the rest is the same as Example 1.

[0049] Comparative Example 1

[0050] This example provides a composite current collector, which consists of a PET layer and two Al layers; the Al layers are located on both side surfaces of the PET layer.

[0051] The specific preparation steps of the above composite current collector are as follows:

[0052] (1) A PET polymer is prepared by esterification and polycondensation of phthalic acid and ethylene glycol. After drying and plasticization, a polymer high molecular PET substrate with a thickness of 6 μm is obtained.

[0053] (2) The two side surfaces of the PET substrate are subjected to corona treatment, and the corona value is ≥50 dynes.

[0054] (3) A metal aluminum layer with a thickness of 1 μm is vacuum-deposited on both sides of the treated PET substrate to obtain a composite current collector.

[0055] Comparative Example 2

[0056] A current collector is specifically an Al layer with a thickness of 8 μm.

[0057] Performance Testing

[0058] (1) Battery assembly:

[0059] Preparation of positive electrode sheets: The positive electrode slurry (98.12% lithium cobalt oxide + 0.35% conductive agent 1 + 0.02% dispersant + 0.56% conductive agent 2 + 0.95% binder) is applied on the current collectors of Examples 1 to 4 and Comparative Examples 1 to 2, dried at 80°C, and then rolled and slit to obtain positive electrode sheets.

[0060] Preparation of negative electrode sheets: The negative electrode slurry (97.5% graphite (containing silicon) + 0.3% thickener + 0.7% binder + 1.5% conductive agent) is coated on the current collector copper foil, dried at 75°C, and then rolled and cut into strips to obtain negative electrode sheets.

[0061] The positive electrode sheets and negative electrode sheets are assembled into a cell, and then a battery is made through processes such as liquid injection, chemical composition, and OCV testing.

[0062] (2) Experimental test:

[0063] 1. In a drying room, immerse the current collectors of Examples 1 to 4 and Comparative Examples 1 to 2 in the electrolyte for 10 minutes, measure the expansion thickness of the pole piece with a micrometer, and compare the thickness of the current collector before and after absorbing the liquid. Calculate the thickness expansion rate according to the following formula:

[0064] Thickness expansion ratio = (thickness after immersion - thickness before immersion) / thickness before immersion × 100%.

[0065] 2. Roller test: The battery cell test needs to be clamped. After the battery cell is well insulated, the test box is turned over at a height of 1 meter, 6 turns / minute (12 times / minute); a total of 600 turns, 1200 times. To pass the roller test, the following standards must be met at the same time: 1) No leakage, no fire, no explosion; 2) △V ≤ 0.1V, internal resistance change rate (△R / initial value) ≤ ± 10%.

[0066] The batteries composed of the current collectors of Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to the above-mentioned drum test, 32 samples were taken for each test, and the number of samples that passed the drum test was calculated.

[0067] The test results of the current collector performance of Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1.

[0068] Table 1 Performance test results of current collectors of Examples 1 to 4 and Comparative Examples 1 to 2

[0069]

[0070]

[0071] As can be seen from Table 1, compared with Comparative Examples 1 to 2, the composite current collectors provided with swellable polymer layers in Examples 1 to 4 of the present invention can achieve volume expansion by absorbing electrolyte, thereby effectively passing the roller safety test, and the roller safety test pass rate is high. In Example 4, since the swellable polymer layer has a thicker thickness, it causes extrusion lithium deposition after swelling due to liquid absorption, especially in steel-shell batteries. Since the shell has rigidity and restrains the winding core, once the winding core is excessively squeezed by the shell, it will cause cyclic lithium deposition of the pole piece. Although cyclic lithium deposition occurred in Example 4, it was able to effectively pass the roller safety test and maintain a high roller safety test pass rate.

[0072] In addition, since the battery will expand in volume and squeeze the current collector in the later stage of the cycle, the swollen polymer layer contained in the composite current collector of the embodiment of the present invention has good tensile properties after swelling due to absorption of liquid, and can play a buffering role, thereby reducing the tensile stress between the pole pieces. At the same time, after squeezing, the polymer layer can also partially release the absorbed electrolyte to reduce the loss of electrolyte. The polymer layer and the swollen polymer layer are both electrically insulating and play a supporting role. Among them, the polymer layer plays a supporting role in the composite current collector and has a low swelling effect; the introduction of the swollen polymer layer not only plays a supporting role, but also has a more significant supporting role due to its large swelling after absorbing the electrolyte.

[0073] In summary, the present invention sets a swelling polymer layer in the middle of the polymer layer, so that the swelling polymer layer replaces part of the polymer layer. Based on the expansion characteristics of the swelling polymer, it expands after absorbing the electrolyte, which can improve the contact effect between the pole pieces and reduce the gap between the battery cell and the shell, effectively solving the problem of low pass rate of the battery roller safety test. The composite current collector obtained by compounding the polymer layer and the swelling polymer layer can effectively improve the safety performance of the battery and increase the pass rate of the battery roller safety test, and has good application prospects in the preparation of positive pole pieces and batteries with high safety performance.

Claims

1. A composite current collector, characterized in that: It comprises a swelling macromolecular layer, a polymer layer and a metal layer; the polymer layer is located on both side surfaces of the swelling macromolecular layer; and the metal layer is located on both side surfaces of the polymer layer.

2. The composite current collector according to claim 1, characterized in that: The swelling degree of the material of the swelling polymer layer is 50-200%.

3. The composite current collector according to claim 1 or 2, characterized in that: The material of the swelling polymer layer includes polystyrene.

4. The composite current collector according to claim 1, characterized in that: The material of the polymer layer includes at least one of polyethylene terephthalate, polypropylene, polyethylene, polyvinyl chloride or polyimide; And / or, the material of the metal layer includes aluminum, copper or a combination thereof.

5. The composite current collector according to claim 1, characterized in that: The ratio of the thickness of the swollen polymer layer to the single layer thickness of the polymer layer is 1:(0.1-6); And / or, the ratio of the thickness of the swollen polymer layer to the single layer thickness of the metal layer is 1:(0.1-3).

6. The composite current collector according to claim 1, characterized in that: The thickness of the swelling polymer layer is 0.5 to 5 μm; and / or, the single layer thickness of the polymer layer is 1 to 3 μm; And / or, the single layer thickness of the metal layer is 0.5-2 μm.

7. A method for preparing a composite current collector according to any one of claims 1 to 6, characterized in that: The following steps are involved: Prepare a polymer layer; modify the surface of one side of the polymer layer, prepare a swollen polymer layer on the surface of the modified polymer layer, and composite the swollen polymer layer with the surface of another modified polymer layer; modify the surface of the other side of the polymer layer, prepare a metal layer on the surface of the modified polymer layer, and obtain the composite current collector.

8. The preparation method according to claim 7, characterized in that: The modification treatment includes at least one of corona treatment, plasma treatment or chemical treatment.

9. A positive electrode sheet, characterized in that: The raw materials for preparing the positive electrode sheet include positive electrode slurry and the composite current collector according to any one of claims 1 to 6.

10. A battery, characterized in that: The battery comprises a positive electrode sheet, an electrolyte and a negative electrode sheet; the positive electrode sheet is selected from the positive electrode sheet described in claim 9.